2021
DOI: 10.1515/med-2021-0241
|View full text |Cite
|
Sign up to set email alerts
|

A four-lncRNA signature for predicting prognosis of recurrence patients with gastric cancer

Abstract: Purpose This study aimed to develop a multi-long noncoding RNA (lncRNA) signature for the prediction of gastric cancer (GC) based on differential gene expression between recurrence and nonrecurrence patients. Methods By repurposing microarray expression profiles of RNAs from The Cancer Genome Atlas (TCGA), we performed differential expression analysis between recurrence and nonrecurrence patients. A prognostic risk prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Suppression of C21orf62-AS1 led to apoptosis in gastric cancer cells. Furthermore, elevated expression of C21orf62-AS1 was associated with significantly reduced median survival time in gastric cancer patients [ 28 ]. Wang et al [ 29 ] found that abnormal methylation-induced downregulation of lncRNA SSTR5-AS1 promotes the progression and metastasis of laryngeal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of C21orf62-AS1 led to apoptosis in gastric cancer cells. Furthermore, elevated expression of C21orf62-AS1 was associated with significantly reduced median survival time in gastric cancer patients [ 28 ]. Wang et al [ 29 ] found that abnormal methylation-induced downregulation of lncRNA SSTR5-AS1 promotes the progression and metastasis of laryngeal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, increasing researches towards ceRNA networks in GICs has not only enhanced our understanding of ceRNA-mediated GICs pathogenesis, but also paved the way for developing novel prognostic biomarkers and therapeutic targets for GICs patients ( 79 ). Indeed, a large number of studies have identified prognostic signatures that predict the OS, metastasis or recurrence of patients with GC, CRC or EC through an integrated analysis of cancer-related ceRNA network ( 41 , 80 , 81 ). However, most of those signatures have not reached the criteria of well-validated effective prognostic models that could improve risk stratification and therapeutic decision making in pre-clinical and clinical practice.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Therefore, prognostic signatures based on lncRNA/circRNA-mediated ceRNA network are increasingly developed to predict metastasis or recurrence of GC patients, thus helping to optimize clinical treatment and management. For example, Chen et al ( 41 ) successfully established a four-lncRNA signature to predict prognosis and distinguish recurrence risk of GC patients with robust performance.…”
Section: Prognostic Signatures Based On Lncrna/circrna-mediated Cerna...mentioning
confidence: 99%